2015
DOI: 10.1177/0042085915618713
|View full text |Cite
|
Sign up to set email alerts
|

Within-District Racial Segregation and the Elusiveness of White Student Return to Urban Public Schools

Abstract: Recent research has determined that racial segregation within school districts has decreased, on average, over the past two decades, even as segregation between school districts has persisted. Although case studies have documented White families' return to urban public schools, with potential implications for segregation patterns, quantitative data on the scope of this trend are lacking. In this article, I examine enrollment and segregation within 97 urban districts from 1990 through 2010. The trend of White r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
0
23
1
2
Order By: Relevance
“…Driven by neoliberal policies encouraging rapid redevelopment in previously neglected urban cores (Lipman, 2011; Posey-Maddox, 2014), gentrification changes the demographic composition of neighborhoods, which has potential implications for changes to school district populations. In a small number of cities, research has found gentrification is indeed related to school demographic change (Billingham, 2015).…”
mentioning
confidence: 99%
“…Driven by neoliberal policies encouraging rapid redevelopment in previously neglected urban cores (Lipman, 2011; Posey-Maddox, 2014), gentrification changes the demographic composition of neighborhoods, which has potential implications for changes to school district populations. In a small number of cities, research has found gentrification is indeed related to school demographic change (Billingham, 2015).…”
mentioning
confidence: 99%
“…Research suggests fragmentation increases macro-level (inter-district) segregation, while actually decreasing micro-level (intra-district and neighborhood-level) segregation, most segregates Blacks from Whites (although Latinos and Asians are increasingly at risk of segregation), and affects access to public goods and services (Bischoff, 2008). In addition, while some research has shown declining rates of segregation within urban districts, in part due to gentrification and the return of Whites to urban schools, others have found this to be limited in most cities (Billingham, 2015).…”
Section: Research Backgroundmentioning
confidence: 99%
“…White urban middle-class parents are increasingly likely to enroll their children in high-status urban public schools, creating new educational competition. Although they perceive this as a progressive act, they are inclined to cluster with other high-status parents in particular schools to extend the reach and effect of their gentrification (Billingham, 2015). The East Bay thus makes for a prime example of the kind of urban space in which "good" and "bad" districts sit cheek-by-jowl, separated only by invisible lines of demarcation.…”
Section: Understanding Districts' Responses To District Hopping: the mentioning
confidence: 99%
“…Researchers in different countries at different stages of urbanization development have different focuses. Sociological scholars focused on the quantitative study of school segregation with much emphasis placed on ethnic and racial dimensions, mainly in America and Europe, including the impact on home-to-school mobility, the differences in charters, and public and private schools [10][11][12][13][14]. School selection is a common problem, existing in many counties, that involves parental choices of schools, school choice mechanisms, impact, and policy and development trends [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%